Invisible students: institutional invisibility and access to education for undocumented children. Issue 1 (6th March 2017) - Meloni, Francesca; Rousseau, Cécile; Ricard-Guay, Alexandra; Hanley, Jill
Abstract : Purpose: In Canada, undocumented children are "institutionally invisible" – their access to education to be found in unwritten and discretionary practices. Drawing on the experience of a three-year university-community partnership among researchers, institutional and community stakeholders, the purpose of this paper is to examine how undocumented children are constructed as excluded from school. Design/methodology/approach: The establishment of this collaborative research space, helped to critically understand how this exclusion was maintained, and highlighted contradictory interpretations of policies and practices. Findings: Proposing the analytical framework of "institutional invisibility", the authors argue that issues of access and entitlement for undocumented children have to be often understood within unwritten and ambiguous policies and practices that make the lives of young people invisible to the institutional entities with which they interact. Originality/value: The notion of institutional invisibility allows the authors to integrate the missing link between questions of access and deservingness. The paper also reflects on the role of action research in both documenting dynamics and pathways of institutional invisibility, as well as in initiating social change – as both horizontal, and vertical mobilisation.